1993
DOI: 10.1111/j.1600-051x.1993.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rinsing time on antiplaque‐antigingivitis efficacy of listerine

Abstract: This double-blind, controlled clinical study compared the effectiveness of 30- and 60-s listerine rinses in both inhibiting the development of, and reducing existing, supragingival plaque and gingivitis, using an experimental gingivitis model. 94 subjects completed this study. For each subject, a modified gingival index, modified Quigley-Hein plaque index and Eastman interdental bleeding index were recorded at baseline and at 2 weeks. Following the baseline examinations, subjects received half-mouth prophylaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 2 publications
(5 reference statements)
1
23
0
Order By: Relevance
“…Clinical trials utilizing experimental gingivitis models have been frequently used as a short-term model to evaluate the antiplaque and antigingivitis efficacy of mouthrinses containing antimicrobial agents. These trials have tested a fixed combination of essential oils, 8,9 0.12% chlorhexidine gluconate, 25,26 cetylpyridinium chloride, 27 0.1% hexetidine, 28 and other noncommercial antimicrobial agents. 29 Therefore, there is enough evidence to support that experimental gingivitis study designs, like long-term models, have been accepted as a valid model to determine and compare efficacy of antiseptic mouthrinses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials utilizing experimental gingivitis models have been frequently used as a short-term model to evaluate the antiplaque and antigingivitis efficacy of mouthrinses containing antimicrobial agents. These trials have tested a fixed combination of essential oils, 8,9 0.12% chlorhexidine gluconate, 25,26 cetylpyridinium chloride, 27 0.1% hexetidine, 28 and other noncommercial antimicrobial agents. 29 Therefore, there is enough evidence to support that experimental gingivitis study designs, like long-term models, have been accepted as a valid model to determine and compare efficacy of antiseptic mouthrinses.…”
Section: Discussionmentioning
confidence: 99%
“…An essential oil-containing mouthrinse (EO) has demonstrated significant antiplaque and antigingivitis efficacy in short-term 7,8,9 and long-term clinical studies 6,10,11,12,13 designed within the guidelines required by the American Dental Association Council on Scientific Affairs for evaluating the clinical efficacy of chemotherapeutic mouthrinses.…”
Section: Introductionmentioning
confidence: 99%
“…This data confirmed that rinsing regularly with an EOcontaining mouthrinse twice a day can reduce the level of blood-borne bacteria caused by a standardized challenge such as that of chewing an apple. It seems reasonable to assume that maintaining good oral hygiene practices, including tooth brushing, flossing and using an effective antimicrobial mouthrinse agent regularly, contributes to preventing periodontal disease, [7][8][9][10][11][12] which, in turn, leads to a lower risk of developing bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of mechanical oral hygiene procedures, the 6-day (short-term) plaque re-growth study is conducted. Similarly, in several studies, a short-term plaque regrowth model was used to assess the chemotherapeutic plaque inhibitory activity of different formulations (1,8,9,13,18).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, non-CHX products like EO and CPC that offer an alternative to long-term use are available (7). The mouthrinses containing EO have received much attention, and their antiplaque effectiveness was demonstrated in numerous clinical trials (5,8,9). Similarly, several studies about the use of a CPC as a cationic surfaceactive agent reported significant improvement in plaque scores and bleeding indices (7).…”
Section: Introductionmentioning
confidence: 99%